“Developing Capabilities”. Inclusive Extracurricular Enrichment Programs to Improve the Well-Being of Gifted Adolescents - Casino-García, Ana María; Llopis-Bueno, María José; Gómez-Vivo, María Gloria; Juan-Grau, Amparo; Shuali-Trachtenberg, Tamar; Llinares-Insa, Lucía I. (Frontiers in Psychology, 2021)
The educational inclusion of gifted students requires not only equity but also emotional accessibility and social participation. However, different studies indicate that gifted students constitute a vulnerable group (for example, there is a higher incidence of bullying). Psychosocial variables are determinants for the development and expression of giftedness, particularly during adolescence. This study analyses the impact of an inclusive extracurricular enrichment programme for gifted secondary school students on the well-being of those adolescents. The programme was based on the enrichment model of Renzulli and Reis (2016). Its objective was to develop a cluster that would facilitate high-achieving learning, in collaboration with teachers, administrators and guidance counsellors from their schools as well as university professors and students, and that would address their emotions and socialisation across the board, benefiting or involving their peers in their regular classrooms. The intervention took place over two years: eight sessions, one afternoon per week, for five months, during each school year. The sample consisted of 47 students from the 1st and 2nd years of Compulsory Secondary Education (Educación Secundaria Obligatoria - ESO) (age M=12.57, age SD=0.82) during the first year and 27 students from the 1st, 2nd and 3rd years of ESO (age M=13.48, age SD=0.94) during the second year; 61.4% were girls. Participants completed a questionnaire before (T1) and (T3) and after (T2) and (T4) of each intervention. The results show better outcomes for psychological and subjective well-being, more positive moods, and a significant reduction in school fears. The results from this study indicate the importance of educational screening and support for gifted students, in order to promote their well-being through collaborative enrichment activities.